A variant in a cis‐regulatory element enhances claudin‐14 expression and is associated with pediatric‐onset hypercalciuria and kidney stones. Issue 6 (21st March 2017) - Ure, Megan E.; Heydari, Emma; Pan, Wanling; Ramesh, Ajay; Rehman, Sabah; Morgan, Catherine; Pinsk, Maury; Erickson, Robin; Herrmann, Johannes M.; Dimke, Henrik; Cordat, Emmanuelle; Lemaire, Mathieu; et al.
Abstract : The image is of a confluent monolayer of rat TAL cells expressing claudin‐14 after the intronic variant, rs78250838:C>T, enriched in children with hypercalciuria and kidney stones. This variant enhances claudin‐14 expression thereby preventing renal tubular calcium reabsorption, increasing urinary calcium excretion and kidney stone risk. Abstract: The greatest risk factor for kidney stones is hypercalciuria, the etiology of which is largely unknown. A recent genome‐wide association study (GWAS) linked hypercalciuria and kidney stones to a claudin‐14 ( CLDN14 ) risk haplotype. However, the underlying molecular mechanism was not delineated. Recently, renal CLDN14 expression was found to increase in response to increased plasma calcium, thereby inducing calciuria. We hypothesized therefore that some children with hypercalciuria and kidney stones harbor a CLDN14 variant that inappropriately increases gene expression. To test this hypothesis, we sequenced the CLDN14 risk haplotype in a cohort of children with idiopathic hypercalciuria and kidney stones. An intronic SNP was more frequent in affected children. Dual luciferase and cell‐based assays demonstrated increased reporter or CLDN14 expression when this polymorphism was introduced. In silico studies predicted the SNP introduced a novel insulinoma‐associated 1 (INSM1) transcription factor binding site. Consistent with this, repeating the dual luciferase assay in the presence of INSM1 further increased reporter expression. Our data suggest that children with the INSM1 binding site within the CLDN14 risk haplotype have a higher likelihood of hypercalciuria and kidney stones. Enhanced CLDN14 expression may play a role in the pathophysiology of their hypercalciuria.